Changing society, changing lives: Three decades of family change in China. (31st May 2021) - Shen, Ke; Cai, Yong; Wang, Feng; Hu, Zhan
Abstract: China has witnessed drastic family changes amidst demographic and socioeconomic transitions unprecedented in its history. Using data from three censuses and a national survey, this paper provided a descriptive documentation about the changing patterns in household size and structures from a synthetic life course perspective. By 2010, people below the age of 5 and in their late 20 s and early 60 s were more likely to live in three‐generation households than in nuclear households compared with their counterparts in 1982, likely due to needs of childcare. The rise in single‐generation households was most noticeable among those in the late 50 s and early 60 s, largely a result of young adults leaving for college or migrating away from home and a heightened aspiration for privacy of both generations. Based on these descriptive findings, future policy directions are discussed including policies to strengthen intergenerational solidarity, to support family caregivers, and to improve community‐based services.